Nerve defect repair by differentiated adipose-derived stem cells and chondroitinase ABC-treated acellular nerves. (2nd June 2016) - Jiang, Liangfu; Zheng, Yan; Chen, Ou; Chu, Tinggang; Ding, Jian; Yu, Qing
Abstract : Objective : To evaluate the effects of differentiated adipose-derived stem cells (dADSC) and chondroitinase ABC (ChABC)-treated acellular nerves (ACN) in building artificial nerves and repairing nerve defects. Methods : ADSC were isolated from the adipose tissue of Wistar rats, induced to differentiate into Schwann-like cells, and implanted into ChABC-treated ACN to repair a 15-mm sciatic nerve defect in Sprague–Dawley rats (the experimental group, group D). The control groups were an autologous nerve transplantation group (group E); ACN (group A), ChABC-treated ACN graft group (group B), and dADSC + ACN (group C). Twelve weeks after surgery, electromyography recordings, tricep surae muscle wet weight recovery rate, and axon counts were measured to evaluate the repair of peripheral nerve defects. Results : The nerve conduction velocity, compound muscle action potentials, tricep surae muscle wet weight recovery rate, and myelinated axon counts in the ChABC-ACN/dADSC group were significantly higher than in the other groups ( P < 0.05), which were all lower than the autologous group ( P < 0.05). Conclusions : The combination of ChABC-treated ACN and dADSC exhibited a synergistic effect in promoting nerve regeneration, and could be an alternative for effective tissue-engineered nerves.